The Role Of Indonesian Army Aviation Towards Handling Covid-19 In The Papua Region - Muhammad Habib Wicaksono; Arifuddin Uksan; Eri Radityawara Hidayat; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The spread of COVID-19 virus has spread throughout the world and affected almost all countries, including Indonesia. One of the areas that was quite badly affected was the Papua region. The Indonesian Army Aviation has an important role in assisting the government towards handling COVID-19 in the targeted region. The purpose of this research is to identify the role of the Indonesian Army Aviation  in handling COVID-19 in the Papua region, the factors that influence the success of its operations, as well as the challenges and obstacles faced in supporting the operation to handle COVID-19 in the Papua region. Handling COVID-19 in the Papua region requires synergy and collaboration from various parties, including the Indonesian Army through Indonesian Army Aviation. Indonesian Army Aviation has an important role in distributing vaccines and medical devices to areas that are difficult to reach in Papua. However, this operation is inseparable from several factors that influence its success, such as geographical conditions and inadequate infrastructure. Challenges and obstacles were also encountered in supporting the operation to handle COVID-19 in the Papua region, including difficulties in taking blood samples and a lack of support from local health institutions. However, the Indonesian Army Aviation continues to strive to overcome these challenges and obstacles through collaboration with various parties, including health agencies and the Indonesian Air Force and the Indonesian Navy. In an effort to deal with COVID-19 in the Papua region, the Indonesian Army Aviation also works with the local government and local community to educate about health protocols and assist in tracing and testing. With good synergy and cooperation.